Restitution of Victims: Funds as Legal Remedy for Consumer in Illegal Digital Investments - Ramma, Natalia (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2026)
In this globalization era, digital investment has become a highly practical alternative for people to invest. This Research Discusses About refunding victims funds as a legal remedies for consumers in illegal investments. There are 3 (three) cases that have similarities, namely the illegal investment fraud mode in Indonesia. This article focused to analyze characteristics of fraudulent investments in digital investments. This article used normative research method with a statute approach, a conceptual approach, and a case approach. The results of the study indicate that digital investment players have shown significant growth in the trading volume of digital assets, such as cryptocurrencies. However, while the digital investment model offers enormous potential, there are also several risks related to market volatility and regulatory uncertainty. Restitution of victims funds as a legal remedy for consumers in illegal investments, as a form of legal protection for victims of illegal digital investment fraud, is a form of protection for the community. This can be realized in various forms, such as fulfilling victims rights, namely compensation, something given to the party who suffered a loss proportional to the amount of the loss.